Learning Management, Covid-19 pandemic - Rifngatin, Ika (Early Childhood Research Journal (ECRJ), 2020)
The purpose of this research is to describe 1) the learning planning during the Covid-19 pandemic in RA Amanah Ummah 8 is correct, 2) the implementation of learning during the Covid-19 pandemic in RA Amanah Ummah 8 is correct, 3) Evaluation of learning during the Covid-19 pandemic at RA Amanah Ummah 8 right.This research is a qualitative descriptive study. Data collection was carried out through observation, interviews, and documentation. The validity of the data in this study used triangulation of sources and triangulation of techniques. Data analysis techniques in this study used data reduction, data presentation and drawing conclusions. The results of this study indicate that: (1) lesson plans prepared during the pandemic use RPPM. (2) the implementation of learning during the Covid-19 pandemic uses 2 learning models, namely through parents and home visit. (3) evaluation of learning during the Covid-19 pandemic using weekly evaluations.